PERBANDINGAN FALAK PRO DAN KONTRA DALAM PENERAPAN KHGT - Ashar, Aidil; Alimuddin, Alimuddin (HISABUNA: Jurnal Ilmu Falak, 2026)
Abstrack This study addresses the recurring issue of differing determinations regarding the start of the Hijri month across Muslim nations, a matter that impacts the collective observance of acts of worship. The central issue concerns how the concept of a Unified Global Hijri Calendar (KHGT) is understood from the perspectives of *ilm falak* (Islamic astronomy) and *fiqh* (Islamic jurisprudence). Two sub-issues are formulated from this core problem: 1) the astronomical and normative *fiqh* foundations underpinning the KHGT concept; and 2) a comparative analysis of the arguments for and against the implementation of the KHGT from an astronomical perspective. These problem formulations serve as a basis for viewing the KHGT not merely as a technical astronomical topic, but also as a religious discourse touching upon dimensions of authority, methodology, and the unity of the Muslim community (*ummah*). This qualitative study employs normative-analytical and comparative approaches. Data were gathered through a literature review covering works on Islamic astronomy, classical and contemporary *fiqh* texts, and academic documents discussing the global Islamic calendar. The analysis examines astronomical foundations—specifically modern *hisab* (astronomical calculation) and crescent moon (*hilal*) visibility criteria—and evaluates them within the framework of Qur’anic evidence, *hadith*, and scholarly views to assess their normative relevance in a contemporary context. The study yields two primary findings. 1) Astronomically, the KHGT is built upon the precision of modern *hisab* calculations, enabling the creation of a global, planned, and predictable Hijri calendar; from a *fiqh* perspective, the concept relies on *ijtihad* (independent legal reasoning) that considers *maqāṣid al-syarī‘ah* (the objectives of Islamic law) and the welfare of the *ummah* in the context of globalization. 2) The divergence between proponents and opponents of the KHGT lies primarily in methodology and approach rather than in the sources of law employed. Proponents emphasize the urgency of calendar unification as a symbol of global unity and the advancement of Islamic civilization, whereas opponents stress the importance of normative caution, the preservation of the *rukyat* (visual sighting) tradition, and the recognition of local authority. The implications of this research suggest that the implementation of KHGT holds potential for development into a more coordinated Islamic calendar system, provided it is established through inclusive scholarly dialogue and cross-national collective *ijtihad*. An integrative approach combining *hisab* (astronomical calculation) and *rukyat* (visual sighting) offers a realistic model for bridging differences, thereby enabling the goal of Muslim unity to be realized without disregarding the rich *fiqh* (Islamic jurisprudence) traditions deeply rooted in Islamic history. Keywords: Comparasion, Agree & Disagree, KHGT